An assessment of the perceptual elements of urban streets based on the context of urban tourism - The case of Sheffield - Huang, Siqi (Frontiers in Public Health, 2024)
Background After COVID-19, more and more travelers are more inclined to walk in cities, and the sensory elements of streets can have a significant impact on urban tourism. Local residents and travelers have different perceptions of the street and preferences for its use. The purpose of this study is to evaluate and analyse the streets from the perspective of locals and travelers. Method In this study, a questionnaire was designed to obtain local residents' and travelers' evaluations of the sensory elements of the street and a quadrant analysis of the street's sensory elements was carried out using the IPA-Kano model. Results The results of the study show that travelers are particularly concerned about maps and signage guidance, while local residents are more concerned about the green environment of the surroundings and how well it is maintained. Conclusion There is a difference in the indicators chosen by the two groups in the results of the comparison between locals and travelers, and this study is hoped to provide some data support for future urban managers and designers to learn from and refer to for street improvements and renewal.